Strategy for Increasing Revenue from Regional Property Utilization Retribution to Enhance Local Own-Source Revenue in North Penajam Paser Regency - Santy; Mujahid; Abdul Majid Bakri (Jurnal Sinar Manajemen, 2025)
This research aims to analyze and formulate effective strategies for enhancing Local Own-Source Revenue (PAD), specifically from retribution on regional asset utilization. It also seeks to identify the supporting and hindering factors in implementing these strategies in Penajam Paser Utara Regency. The study's primary focus is on how the local government can maximize potential revenue from its owned assets to achieve greater fiscal independence. To accomplish these objectives, the research employed a qualitative approach with comprehensive data collection methods, including in-depth interviews, observation, and documentation. Interviews were conducted with various key stakeholders, such as the Head of the Regional Finance and Asset Agency, the Head and Sub-Head of the Asset Division, Staff from the Retribution Collection Division, Business Operators, and the General Public. All collected data were subsequently analyzed using the Miles and Huberman interactive model, which allowed the researchers to identify patterns, themes, and inter-variable relationships in depth. The research findings indicate that Penajam Paser Utara Regency has implemented a comprehensive strategy to increase revenue from regional asset utilization retribution. This strategy encompasses efforts to improve taxpayer compliance and strict law enforcement, optimize regional asset management, leverage information technology for efficiency, and foster collaboration and synergy among local government units (SKPDs) and relevant parties, all supported by clear collection procedures. The main supporting factors for the strategy's success include effective existing policies, improved asset management, implemented technological innovations, and positive service quality that satisfies the community. Despite these efforts, the study also identified significant hindering factors. Key challenges include the sub-optimal utilization of regional assets, insufficient socialization and understanding among retribution payers regarding their obligations, and compliance issues often influenced by economic fluctuations. Therefore, this research concludes that to maximize the PAD potential from regional asset utilization retribution, Penajam Paser Utara Regency needs to address these obstacles through more targeted and sustainable efforts.